Question 6

loading...

Prev/Next links

Jambmaths question: 

Simplify $1-\left( 2\tfrac{1}{3}\times 1\tfrac{1}{4} \right)+\tfrac{3}{5}$

Option A: 

$-1\tfrac{19}{60}$

Option B: 

$-2\tfrac{7}{15}$

Option C: 

$-1\tfrac{1}{15}$

Option D: 

$-2\tfrac{31}{60}$

Jamb Maths Solution: 

$\begin{align}  & 1-\left( 2\tfrac{1}{3}\times 1\tfrac{1}{4} \right)+\tfrac{3}{5}=1-\left( \tfrac{7}{3}\times \tfrac{5}{4} \right)+\tfrac{3}{5} \\ & =1-\tfrac{35}{12}+\tfrac{3}{5} \\ & =\tfrac{60-175+36}{60} \\ & =-\tfrac{79}{60}=1\tfrac{19}{60} \end{align}$

Jamb Maths Topic: 
Year of Exam: